Structural considerations to minimise the risk of horizontal cracks in the wall of circular concrete tanks. (June 2022) - Rodd, James; Castel, Arnaud
Abstract: The inspection of on-ground circular concrete tanks by the authors has shown that the formation of horizontal cracks in tank walls is a common serviceability issue in Australia. These cracks often lead to leakage or durability-related issues that impact the service life of tanks. In this research, a harmonised design approach is provided for designers to consider the contribution of different parameters such as liquid pressure and volumetric changes of concrete, autogenous shrinkage, solar, seasonal and thermal process loads to the serviceability design. A practical model has been developed to predict the vertical serviceability bending moments and the width of horizontal cracks in the wall of tanks without the need to perform complex Finite Element (FE) modelling. This model has been developed by establishing a mathematical correlation between the design inputs and results of FE analysis of 320 tanks. In addition, risk factors in the formation of horizontal cracks on the internal and external faces of tanks were investigated, and recommendations for minimising the risk of horizontal cracks are provided.